2005
DOI: 10.2741/1636
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in NASH

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease observed in the clinical practice of hepatology. The coexistence of metabolic syndrome in this cohort of patients has made insulin resistance central to the pathogenesis of these disorders. The metabolic consequence of insulin resistance is impaired hepatic glucose output and abnormal lipid handling. In the face of continued metabolic insults the normal hepatic regulatory mechanism gets overwhelmed and fat accumulates in the hepatocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 75 publications
0
28
0
1
Order By: Relevance
“…No perfect theory exists for all its clinical manifestations [13,14] . At present, IR along with hepatocyte fatty degeneration is believed to be a key factor in the occurrence and development of fatty liver disease [15,16] . Research indicates [10] that IR exits in about 98% of patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…No perfect theory exists for all its clinical manifestations [13,14] . At present, IR along with hepatocyte fatty degeneration is believed to be a key factor in the occurrence and development of fatty liver disease [15,16] . Research indicates [10] that IR exits in about 98% of patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…12 OSA is also independently associated with insulin resistance and type 2 diabetes mellitus in obese individuals, 2,44-46 and CIH exacerbates insulin resistance in obese rodents. 11 Because hepatic steatosis is a known consequence of insulin resistance, 16,47,48 a CIH-induced increase in insulin resistance in combination with oxidative stress may lead to NASH in obese patients with OSA and in obese mice exposed to CIH. However, our new findings indicate that, in the absence of obesity, CIH does not result in hyperinsulinemia and liver steatosis (Tables 1 and 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of NASH remains unclear. Nowadays, lipid metabolism abnormality, insulin resistance and oxidative stress and lipid peroxidation reaction [4][5][6][7][8] are thought to play an important role in the pathogenesis of NASH [9,10] . It was reported that the change of intestinal environment may play a role in NASH, which may be a cause of enterogenous endotoxemia [11,12] .…”
Section: Introductionmentioning
confidence: 99%